Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\frac{x^2-yz}{\left(x+y\right)\left(x+z\right)}+\frac{y^2-xz}{\left(y+z\right)\left(y+x\right)}+\frac{z^2-xy}{\left(z+x\right)\left(z+y\right)}\)
\(=\frac{\left(x^2-yz\right)\left(y+z\right)+\left(y^2-xz\right)\left(z+x\right)+\left(z^2-xy\right)\left(x+y\right)}{\left(x+y\right)\left(y+z\right)\left(z+x\right)}\)
\(=\frac{x^2y+x^2z-y^2z-yz^2+y^2z+y^2x-xz^2-x^2z+z^2x+z^2y-x^2y-xy^2}{\left(x+y\right)\left(y+z\right)\left(z+x\right)}\)
\(=\frac{0}{\left(x+y\right)\left(y+z\right)\left(z+x\right)}=0\)
Vậy : \(A=0\)
\(\frac{(x^2-yz)(y+z)}{(x+y)(x+z)(y+z)}\) = \(\frac{(y^2-xz)(x+z)}{(x+y)(x+z)(y+z)}\)= \(\frac{(z^2-xy)(x+y)}{(x+y)(x+z)(y+z)}\)
\(a,\left(x+y\right)^2+\left(x-y\right)^2=x^2+2xy+y^2+x^2-2xy+y^2=2\left(x^2+y^2\right)\)\(b,2\left(x-y\right)\left(x+y\right)+\left(x+y\right)^2+\left(x-y\right)^2=2x^2-2y^2+x^2+2xy+y^2+x^2-2xy+y^2=3x^2\)\(c,\left(x-y+z\right)^2+\left(z-y\right)^2+2\left(x-y+z\right)\left(y-z\right)=\left[\left(x-y+z\right)-\left(z-y\right)\right]^2=\left(x-2y\right)^2\)
a) \(\left(x+y\right)^2+\left(x-y\right)^2\)
=\(\left(x^2+2xy+y^2\right)+\left(x^2-2xy+y^2\right)\)
=\(x^2+2xy+y^2+x^2-2xy+y^2\)
\(2x^2+2y^2=2\left(x^2+y^2\right)\)
b) \(2\left(x-y\right)\left(x+y\right)+\left(x+y\right)^2+\left(x-y\right)^2\)
\(=\left(x-y\right)^2+2\left(x-y\right)\left(x+y\right)+\left(x+y\right)^2\)
=\(\left[\left(x-y\right)+\left(x+y\right)\right]^2\)
= \(\left(x-y+x+y\right)^2\)
\(=2x^2\)
c) \(\left(x-y+z\right)^2+\left(z-y\right)^2+2\left(x-y+z\right)\left(y-z\right)\)
\(=\left(x-y+z\right)^2-2\left(x-y+z\right)\left(z-y\right)+\left(z-y\right)^2\)
\(=\left[\left(x-y+z\right)-\left(z-y\right)\right]^2\)
= \(\left(x-y+z-z+y\right)^2=x^2\)
Bài làm:
Ta có: \(\left(x-y+z\right)^2+\left(z-y\right)^2+2\left(x-y+z\right)\left(y-z\right)\)
\(=\left(x-y+z\right)^2+2\left(x-y+z\right)\left(y-z\right)+\left(y-z\right)^2\)(hằng đẳng thức đầu)
\(=\left(x-y+z+y-z\right)^2=x^2\)
\(\left(x-y+z\right)^2+\left(z-y\right)^2+2\left(x-y+z\right)\left(y-z\right)\)
\(=\left(x-y+z\right)^2+2\left(x-y+z\right)\left(y-z\right)+\left(y-z\right)^2\)
\(=\left[\left(x-y+z\right)+\left(y-z\right)\right]^2=\left(x-y+z+y-z\right)^2=x^2\)
\(x+y+z=0\Rightarrow\hept{\begin{cases}x=-\left(y+z\right)\\y=-\left(z+x\right)\\z=-\left(x+y\right)\end{cases}}\)
\(\Rightarrow P=\frac{x^2+y^2+z^2}{\left(x-y\right)^2+\left(y-z\right)^2+\left(z-x\right)^2}=\frac{\left[-\left(y+z\right)\right]^2+\left[-\left(z+x\right)\right]^2+\left[-\left(x+y\right)\right]^2}{\left(x-y\right)^2+\left(y-z\right)^2+\left(z-x\right)^2}=\frac{\left(y+z\right)^2+\left(z+x\right)^2\left(x+y\right)^2}{\left(x-y\right)^2+\left(y-z\right)^2+\left(z-x\right)^2}=\frac{-\left[\left(y-z\right)^2+\left(z-x\right)^2+\left(x-y\right)^2\right]}{\left(x-y\right)^2+\left(y-z\right)^2+\left(z-x\right)^2}=-1\)
\(a,2\left(x-y\right)\left(x+y\right)+\left(x+y\right)^2+\left(x-y\right)^2\)
\(=2\left(x^2-y^2\right)+x^2+2xy+y^2+x^2-2xy+y^2\)
\(=2x^2-2y^2+x^2+2xy+y^2+x^2-2xy+y^2\)
\(=4x^2\)
a,2(x-y)(x+y)+(x+y)2+(x-y)2
=2(x2-y2)+x2+2xy+y2+x2-2xy+y2
=4x2
b,=x2
\(x+y+z=0\)
\(\Rightarrow\left(x+y+z\right)^2=0\)
\(x^2+y^2+z^2+2\left(xy+yz+zx\right)=0\)
\(x^2+y^2+z^2=-2\left(xy+yz+zx\right)\)
\(\frac{x^2+y^2+z^2}{\left(y-z\right)^2+\left(z-x\right)^2+\left(x-y\right)^2}\)
\(=\frac{-2\left(xy+yz+zx\right)}{2\left(x^2+y^2+z^2\right)-2\left(xy+yz+xz\right)}\)
\(=\frac{-2\left(xy+yz+zx\right)}{2\left[-2\left(xy+yz+zx\right)\right]-2\left(xy+yz+xz\right)}\)
\(=\frac{-2\left(xy+yz+zx\right)}{-4\left(xy+yz+zx\right)-2\left(xy+yz+xz\right)}\)
\(=\frac{-2\left(xy+yz+zx\right)}{-6\left(xy+yz+zx\right)}\)
\(=\frac{1}{3}\)
Ta có: \(x+y+z=0\)
\(\Rightarrow x+y=-z\)
\(\Rightarrow\left(x+y\right)^2=\left(-z\right)^2\)
\(x^2+2xy+y^2=z^2\)
\(x^2+y^2-z^2=-2xy\)
\(\frac{2x^2y+2xy^2}{x^2+y^2-z^2}\)
\(=\frac{2xy\left(x+y\right)}{-2xy}\)
\(=\frac{-2xyz}{-2xy}\)
\(=z\)
\(=\left[\left(x-y-z\right)+\left(y-z\right)\right]^2\)
\(=\left(x-2z\right)^2\)
(x - y - z)2 + (y - z)2 + 2(y - z).(x - y - z)
= (x - y - z)2 + 2(y - z).(x - y - z) + (y - z)2
= (x - y - z + y - z)2
=(x - 2z)2
~ Học tốt ~